Il manifesto per l'università: CEI e CRUI in dialogo per l’università del XXI secolo = The Manifesto for the University : CEI and CRUI in dialogue for the 21st century university - Mingardo, Letizia (Rivista di scienze dell'educazione, 2020)
In 2019 the Conference of Italian Bishops and the Conference of Italian University Rectors approved the Manifesto for the University, which is a valuable occasion to reflect on the state of the university system in Italy and on the most opportune ways of identifying and addressing the massive educational challenges of the 21st century. In elaborating nine fundamental objectives, the Manifesto calls for a university that is not just a passive receptacle for the contemporary dynamics of globalization, digitalization, and secularization, but one that knows how to propositively, and where appropriate, reactively, participate under the guidance of the principle of solidarity humanism.